Peran library, archives, museums dalam pelestarian naskah kuno di Kalimantan Barat - Atiqa Nur Latifa Hanum; Antonius Totok Priyadi; Aliyah Nur’aini Hanum; Aji Ali Akbar (Berkala Ilmu Perpustakaan dan Informasi, 2023)
Introduction.There were still many ancient manuscripts that are kept privately by the community.The low awareness and response to the preservation of ancient manuscripts was a severe threat.They were the potential for the extinction of ancient manuscripts due to intentional or accidental reasons.The purpose of this paper it to describe the role of Library, Archive and Museum (LAM) in preserving ancient manuscripts in West Kalimantan. Data collection methods. A qualitative approach, through participatory observation, interviews with seven informants, and literature studies was conducted. Data analysis. Reduction, presentation, and drawing conclusions were conducted as parts of data anaylsis. The validity used source triangulation, cross-checking on informants. Results and discussion. LAM collected ancient manuscripts through compensation, exchange, deposit, grants, and copying.They were still many ancient manuscripts kept privately and preserved in a simple way among the community so that they are vulnerable and be the threat of extinction. Therefore, LAM needed to optimize its role as a collector, educator, conservator, and translator in order to maintain the integrity and extend the life of ancient manuscripts. Conclusion. Strategies that are possibly implemented includethe collaboration between LAM to optimize the role of LAM to increase public awareness and knowledge in preserving ancient manuscripts.